2020
DOI: 10.1017/s095026882000117x
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension with the severity and fatality of SARS-CoV-2 infection: A meta-analysis

Abstract: Hypertension is a common comorbidity in COVID-19 patients. However, the association of hypertension with the severity and fatality of COVID-19 remain unclear. In the present meta-analysis, relevant studies reported the impacts of hypertension on SARS-CoV-2 infection were identified by searching PubMed, Elsevier Science Direct, Web of Science, Wiley Online Library, Embase and CNKI up to 20 March 2020. As the results shown, 12 publications with 2389 COVID-19 patients (674 severe cases) were included for the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 33 publications
5
74
1
9
Order By: Relevance
“…This enzyme is widely expressed in different organs which may make them susceptible to this virus. Due to some documents using ACE-Inhibitors and Angiotensin receptor blockers (ARBs) can increase the expression of ACE-2 which may increase the field of binding virus and makes the host susceptible (14). Based on these, in fact, ACE-2 acts by catalyzing AngII to Ang1-7 and increases its anti-inflammatory effect (15).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is widely expressed in different organs which may make them susceptible to this virus. Due to some documents using ACE-Inhibitors and Angiotensin receptor blockers (ARBs) can increase the expression of ACE-2 which may increase the field of binding virus and makes the host susceptible (14). Based on these, in fact, ACE-2 acts by catalyzing AngII to Ang1-7 and increases its anti-inflammatory effect (15).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 85.7% of the severe patients had comorbidities. This may be due to abnormal immune function and increased susceptibility to SARS-CoV-2 in patients with comorbidities [26,27]. In addition, COVID-19 damage to the lungs can aggravate some comorbidities, such as chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no meta-analysis specifically designed to assess the role of age, sex and health condition of the studied populations with a comprehensive list of potential clinical predictors of mortality in hospitalized patients with confirmed COVID-19 has been reported. Thus far, Zhang et al [ 11 ] observed that the association between hypertension and mortality was stronger in studies with patients who are less than 50 years old (OR = 6.4) than in those 50 years old and older (OR = 2.6), although the authors included only six studies in their meta-analysis. In another study, Pranata et al [ 12 ] used meta-regression methods and found an association between hypertension and increased composite worse outcome, including mortality, which is influenced by sex (more strongly when the population is less than 55% male patients), but not age.…”
Section: Introductionmentioning
confidence: 99%